Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L; Schulte, M; Raschi, A; Slee, N; Rennenberg, H; Polle, A (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco

Antioxidative systems, pigment and protein contents in leaves of adult mediterranean oak species (Quercus pubescens and Q. ilex) with lifetime exposure to elevated CO2 - Schwanz, P; Polle, A (New Phytologist, 1998)
The aim of the present study was to investigate the effects of elevated CO2 on the antioxidative systems and the contents of pigments, soluble protein and lipid peroxidation in leaves of adult oaks, Quercus pubescens and Quercus ilex, grown at naturally enriched CO2 concentrations. For this purpose, a field study was conducted at two CO2 springs in Central Italy. Measurements of the pre-dawn water potentials indicated less drought stress in trees close to CO2 springs than in those grown at ambient CO2 concentrations. Most leaf constituents investigated showed significant variability between sampling dates, species and sites. The foliar contents of protein and chlorophylls were not affected in trees grown close to the CO2 vents compared with those in ambient conditions. Increases in glutathione and other soluble thiols were observed, but these responses might have been caused by a low pollution of the vents with sulphurous gases. At CO2 vents, glutathione reductase was unaffected, and superoxide dismutase activity was significantly diminished, in both species. Generally, the activities of catalase, guaiacol peroxidase and ascorbate peroxidase as well as the sum of dehydroascorbate and ascorbate were decreased in leaves from trees grown in naturally CO2-enriched environments compared with those grown at ambient CO2 concentrations. The reduction in protective enzymes did not result in increased lipid peroxidation, but increased monodehydroascorbate radical reductase and dehydroascorbate reductase activities found in leaves of Q. pubescens suggest that the smaller pool of ascorbate was subjected to higher turnover rates. These data show that changes in leaf physiology persist, even after lifetime exposure to enhanced atmospheric CO2. The results suggest that the down-regulation of protective systems, which has also previously been found in young trees or seedlings under controlled exposure to elevated CO2 concentrations, might reflect a realistic response of antioxidative defences in mature trees in a future high-CO2 world.
Keywords: antioxidants; carbon dioxide enrichment; Drought; Oxidative stress; Quercus spp. (holm oak - white oak)

Diurnal fluctuations of secondary photooxidants in air and of detoxification systems in the foliage of Mediterranean forest trees - Junkermann, Wolfgang; Polle, A (Atmospheric Environment, 1997)
s-phase peroxide mixing ratios were measured in the canopy area of a Mediterranean oak/pine fo.rest. Concurrently the activities of cell wall localized peroxidases, which protect leaves from external oxidants, were investigated. The diurnal cycles of peroxidase activity showed a strong decrease when the gas-phase concentration of highly phytotoxic hydroxy hydroperoxides increased. These results suggest that ambient gas-phase mixing ratios of organic peroxides may injure the plants’ oxidative defence system
Keywords: antioxidant protection; organic peroxides; peroxidase activity